Through our eyes : African American men's experiences of race, gender, and violence - Garfield, Gail, 1964- (Book collections on Project MUSE., 2010)
Through Our Eyes provides a view of black men's experiences that challenges scholars, policy makers, practitioners, advocates, and students to grapple with the reality of race, gender, and violence in America. This multi-level analysis explores the chronological life histories of eight black men from the aftermath of World War II through the Cold War and into today. By appreciating the significance of how African American men live through what it means to be black and male in America, this book envisions the complicated dynamics that devalue their lives, those of their family, and soc.